Coastal Communications: Teaching Civic Scientific Literacy in English and Environmental Science and Resource Management Classes - Stacey Anderson; Kiki Patsch (Journal of the Assembly for Expanded Perspectives on Learning, 2023)
Named after the national park that lies just off of our Ventura County shores, California State University Channel Islands draws faculty who are committed to integrating the coast into their teaching and research. This context has inspired our interdisciplinary collaboration as teacher-scholars who hail from separate departments (English and Environmental Science and Resource Management). Our work together is designed to amplify civic scientific literacy in our classrooms as a means of elevating discourse on the growing challenges that threaten our coastal communities.